Assessment and management of pain in children and adolescents with bleeding disorders: a cross‐sectional study from three haemophilia centres. (20th July 2015) - Rambod, M.; Forsyth, K.; Sharif, F.; Khair, K.
Abstract : Introduction: Pain is a major clinical problem in patients with bleeding disorders. This study aimed to determine the level of pain and how it is managed in children and adolescents with bleeding disorders. Methods: This cross‐sectional study was performed in three haemophilia centres (one in Shiraz and two in London).The data were collected using questions about pain management and Wong‐Baker Faces Pain Rating Scale at routine clinical review as well as attendance for bleed treatment in summer 2014. Results: This study indicated no difference among the three haemophilia centres regarding having pain, however, a significant difference was found among them concerning the mean score of pain intensity. Among the 154 subjects, 20.8% had pain on the study day, most reporting moderate levels of pain. The study participant's most frequently described their pain as aching, dull, throbbing and stabbing. Moreover, 84.38% of pain was experienced in joints and the most common painful joints were knees, ankles, elbows, hands and hips. The most common pain relief strategies included factor administration, immobilization and rest, ice packs and analgesia. Pain was significantly associated with disease severity and age. Conclusion: As the intensity of pain in on‐demand patients was highest, using prophylaxis treatment is suggested. Moreover, adolescent patients reported more pain; giving more self‐care information to them and their parents is recommended. Since little evidence was published for pain assessment and management in children and adolescents with bleeding disorders, more research is recommended.